PROFIL MEDIA PEMBELAJARAN DI SD N 01 KEBONDALEM KABUPATEN PEMALANG - Maghfiroh, Dwi Ovi; Wijayanti, Arfilia; Budiman, Muhammad Arief (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
The purpose of this study was to determine the learning media in in State Elementary School 01 Kebondalem. As well as describing and analyzing the profile of learning media in State Elementary School 01 Kebondalem. This research is a type of qualitative research with a descriptive approach. The research instruments used are observation sheets, interviews with teachers, and questionnaires. In this study, researchers found data that in State Elementary School 01 Kebondalem teachers use the Whats-App Group platform as a learning space. The types of learning media used are visual and audiovisual, from the data that has been obtained from grade one to grade six there are 16 learning media with the percentage of types of learning media in the form of visual as much as 37% and audiovisual learning media as much as 62% In conclusion, the results of the analysis of learning media in SD Negeri 01 Kebondalem, there are two types of learning media used by teachers, namely the type of visual media and audio-visual media. With the percentage of visual media types as much as 37% and audiovisual learning media as much as 62%.